Konstruksi Kesadaran Masyarakat Islam berbasis Zakat Dalam Mencapai Keberdayaan Ekonomi - Fajar, M.Samson (Ath Thariq Jurnal Dakwah dan Komunikasi, 2022)
Empowerment, conceptually is empowerment derived from the word 'power' (power or empowerment). In this context, empowerment is a process and purpose. Empowerment process is a series of activities to strengthen the power or empowerment of weaker groups in society, including individuals who experience poverty problem. For the purpose of empowerment refers to circumstances or results to be achieved by a social change, ie an empowered community, have power or have the knowledge and ability in meeting the needs of economic life is both physical, and social. While the meaning of charity in the context of jurisprudence is the amount of certain assets that are required of God handed to the person entitled. From the definition above, the economic empowerment of community-based charity is a process or series of activities to raise the economic potential of community both in personal life (syakhsîah), family (usroh), community (umma) and even state and nation to create an empowered community economy, based on the values ​​of zakat.